2021
DOI: 10.1055/s-0040-1721004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Intraoperative Aneurysm Rupture, Aneurysm Remnant, and Brain Ischemia following Microsurgical Clipping of Intracranial Aneurysms: Single-Center, Retrospective Cohort Study

Abstract: Background and Study Aims Complete microsurgical clip occlusion of an aneurysm is one of the most important challenges in cerebrovascular surgery. Incorrect position of clip blades as well as intraoperative aneurysm rupture can expose the patient to serious complications such as rebleeding in case of aneurysm remnant and cerebral ischemia in case of occlusion of branching arteries or perforators. The aim of this study was to identify independent predictors of surgery-derived complications (aneurysm remnant and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… Laur et al 273 312 Fifteen international cohorts Absolute risk of ruptured intracranial aneurysms in growth based on triple-S prediction model. Wojciech et al 278 147 Maria Sklodowska-Curie Hospital The study identified independent predictors of surgically derived complications (residual aneurysm and cerebral ischemia) and intraoperative aneurysm rupture. Duan et al 279 107 National Taiwan University Hospital To study the clinical manifestations and genetic characteristics of patients with TAA and dissection in Taiwan.…”
Section: Clinical Cohort Studymentioning
confidence: 99%
See 2 more Smart Citations
“… Laur et al 273 312 Fifteen international cohorts Absolute risk of ruptured intracranial aneurysms in growth based on triple-S prediction model. Wojciech et al 278 147 Maria Sklodowska-Curie Hospital The study identified independent predictors of surgically derived complications (residual aneurysm and cerebral ischemia) and intraoperative aneurysm rupture. Duan et al 279 107 National Taiwan University Hospital To study the clinical manifestations and genetic characteristics of patients with TAA and dissection in Taiwan.…”
Section: Clinical Cohort Studymentioning
confidence: 99%
“…Wojciech et al 278 analyzed 147 patients who chose microsurgical clipping for intracranial aneurysms over a five-year period to determine the independent predictors of surgically derived complications (residual aneurysm and cerebral ischemia) and intraoperative aneurysm rupture. They found that an increase in aneurysm volume with a cutoff of 9 mm ( P = 0.009; odds ratio [OR]: 0.644) and irregular dome shape ( P = 0.003; OR: 4.242) were independently associated with cerebral ischemia and residual aneurysm in 13.6% and 17.3% of the cohort, respectively.…”
Section: Clinical Cohort Studymentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Moreover, the occurrence of ischemic complications resulting from inadvertent stenosis or occlusion of parent or perforating arteries and aneurysm remnants after elective unruptured intracranial aneurysm clipping procedures underlines the importance of structured education and skill training. [5][6][7][8][9] Consequently, there is an unmet demand to train future cerebrovascular neurosurgeons outside the actual operating room in safely performing clipping of intracranial aneurysms. In the past, several models have been proposed to improve microsurgical skills.…”
Section: Dodier Et Almentioning
confidence: 99%
“…Intracranial aneurysm due to intracranial vascular wall damage is the leading cause of intracranial hemorrhage, and is more likely to occur in people aged between 40 and 60 years old (1)(2)(3). Most intracranial aneurysms are located around the Wills ring, but a few are located deep in the lateral or longitudinal fissure pool or brain parenchyma, which are also known as distal aneurysms and account for about 1.5-9% of the total number of intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%